Firmicutes Dysbiosis After Chlorhexidine Prophylaxis in Healthy Patients Submitted to Impacted Lower Third Molar Extraction - Neves, Carlos Augusto das; Alves, Carlos Henrique; Rocha, Natália Conceição; Rizzardi, Karina Ferreira; Russi, Karolyne Larissa; Palazzi, Alexandre Augusto Albigiante; Parisotto, Thaís Manzano; Girardello, Raquel (Frontiers in Cellular and Infection Microbiology, 2021)
Prophylaxis with antiseptic and antibiotic therapy is common in third molar surgeries, despite lack of consensus among professionals and researchers about the need and the protocol for healthy patients. We evaluated 11 patients submitted to impacted third molar extraction, among 3 experimental phases, under prophylactic therapy with 0.12% chlorhexidine and amoxicillin. Our results showed no statistically significant reduction of total bacteria charge in the oral cavity, after prophylactic therapy with antiseptic and antibiotic. In addition, we observed a diversity response among the patients, suggesting a microbiota dysbiosis, mainly after amoxicillin use, that may be responsible for selection of antibiotic resistant microorganisms. Our results alert for an overuse of antibiotics by dentists and for a need of better evaluation of the protocols available.